The Leadership Role of the Head of Study Program in Improving Student Learning Motivation: A Systematic Literature Review - Muhammad Difa Izzati; Siti Zahra Maulida; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the crucial role of the Head of Study Program (Kaprodi) leadership in influencing and enhancing student learning motivation, particularly in the context of Islamic higher education. This study uses a systematic literature review (SLR) method with a qualitative-descriptive approach. Primary and secondary data sources come from 42 reputable scientific journal articles published between 2020 and 2025. The data analysis techniques used are content analysis and narrative synthesis, based on transformational leadership theory and expectancy theory. The results show that the Head of Study Program's leadership plays a role through three dimensions: the Instructional Dimension (curriculum optimization and lecturer quality), the Managerial Dimension (creating a collaborative and supportive academic climate), and the Transformative Dimension (providing role models, inspiration, and intellectual stimulation). This role significantly increases students' intrinsic and extrinsic motivation. The practical contribution of this study is to formulate a Head of Study Program leadership model that is adaptive to the demands of the digital era in Islamic Religious Higher Education